Targeted synthesis of 3,3'-, 3,4'- and 3,6'-phenylpropanoid sucrose esters - Wong, Kathy Pooi Wen (2022)
In this study, we report on an orthogonal strategy for the precise synthesis of 3,3'-, 3,4'-, and 3,6'-phenylpropanoid sucrose esters (PSEs). The strategy relies on carefully selected protecting groups and deprotecting agents, taking into consideration the reactivity of the four free hydroxyl groups of the key starting material: di-isopropylidene sucrose 2. The synthetic strategy is general, and potentially applies to the preparation of many natural and unnatural PSEs, especially those substituted at 3-, 3'-, 4'- and 6'-positions of PSEs.